Democracy and Executive Power: Administrative Policymaking in Comparative Perspective - Rose-Ackerman, Susan (Revista de Derecho Público: Teoría y método, 2022)
This essay on executive rulemaking procedures in the US, the UK, France, and Germany examines how administrative and constitutional law interact when the executive makes policy under delegated authority. Given their differing constitutional structures and legal frameworks, the political incentives for policymaking accountability differ. The US is a separation-of-powers presidential system. Germany and the UK are parliamentary systems with and without written constitutions. The common law underpins the UK’s unwritten constitution. France has a strong president with a relatively weak parliament. The US separation of powers generated statutory requirements for notice-and-comment rulemaking. The legislatures in the German and UK parliamentary systems have little incentive to enact such constraints on their own cabinets. The French system lacks required procedures as well. However, even if political incentives suggest that sitting politicians will have little interest in such reform, the need for greater accountability to the public remains. This essay, drawing on the author’s recent book Democracy and executive power, describes these cross-country differences and argues for ways to produce more democratically responsible executive policymaking. Those concerned about the future of representative democracy should include reform of executive rulemaking procedures in their list of priorities. Structural issues linked to the openness and accountability of regulatory bodies and cabinet departments should not be ignored in the heat of day-to-day crises that soak up the headlines.